Investigation for the transcultural self-efficacy of nurses in Guizhou, China - Juan Li; Bei Wu; Zhuang He; Jiru Liu; Rong Xiao; Yong Luo (Elsevier, 2020)
Aim: As conflict caused by cultural diversity among patients in China continues to rise, hospitals are in urgent need for improvement of transcultural efficacy among nurses. This study aims to evaluate the transcultural self-efficacy of nurses working in the tertiary general hospital in Guizhou Province, an ethnic minority region in western China, and to identify whether nurses' demographic characteristics affect their transcultural self-efficacy. Method: We used the Chinese version of the Transcultural Self-Efficacy Tool (TSET-CV) to survey 1,190 in-service nurses. Results: Results showed that the level of transcultural self-efficacy of the nurses was generally moderate; few of the nurses had high or low transcultural self-efficacy. The nurses' transcultural self-efficacy was affected by demographic variables, including age, marital status, employment type, income, work experience, and whether or not they were head nurses. Having a stable work environment, a stable marriage, a good educational background, and a high-ranked professional title were associated with increased transcultural self-efficacy. Conclusion: Nursing administrators in hospitals should offer continuing education on transcultural nursing according to nurses' demographic characteristics and the SEST scores.